Main Factors Predicting Nonresponders to Autologous Cell Therapy for Critical Limb Ischemia in Patients With Diabetic Foot - Dubský, Michal; Fejfarová, Vladimíra; Bem, Robert; Jirkovská, Alexandra; Nemcová, Andrea; Sutoris, Karol; Husáková, Jitka; Skibová, Jelena; Jude, Edward B (Angiology, 2021)
Autologous cell therapy (ACT) is a new treatment for patients with no-option critical limb ischemia (NO-CLI). We evaluated the factors involved in the nonresponse to ACT in patients with CLI and diabetic foot. Diabetic patients (n = 72) with NO-CLI treated using ACT in our foot clinic over a period of 8 years were divided into responders (n = 57) and nonresponders (n = 15). Nonresponder was defined as an insufficient increase in transcutaneous oxygen pressure by <5 mm Hg, 3 months after ACT. Patient demographics, diabetes duration and treatment, and comorbidities as well as a cellular response to ACT, limb-related factors, and the presence of inherited thrombotic disorders were compared between the 2 groups. The main independent predictors for an impaired response to ACT were heterozygote Leiden mutation (OR 10.5; 95% CI, 1.72-4) and homozygote methylenetetrahydrofolate reductase (MTHFR 677) mutation (OR 3.36; 95% CI, 1.0-14.3) in stepwise logistic regression. Univariate analysis showed that lower mean protein C levels (P = .041) were present in nonresponders compared with responders. In conclusion, the significant predictors of an impaired response to ACT in diabetic patients with NO-CLI were inherited thrombotic disorders.
Keywords: Activated Protein C Resistance; Treatment Failure; heterozygot; hodnocení rizik; Male; homozygot; mutace; neúspěšná terapie; Risk Assessment; Risk Factors; Heterozygote; risk factors; faktor V; Cell Transplantation; rezistence k aktivovanému proteinu C; Critical Illness; ischemie; inherited thrombotic disorders; Aged; mužské pohlaví; senioři; Diabetic Foot; Factor V; Homozygote; Ischemia; methylentetrahydrofolátreduktasa (NADPH2); autologní transplantace; lidé; kritický stav; ženské pohlaví; Humans; critical limb ischemia; cell therapy; dědičné koagulopatie; rizikové faktory; Transplantation, Autologous; Methylenetetrahydrofolate Reductase (NADPH2); Mutation; Female; lidé středního věku; transplantace buněk; Blood Coagulation Disorders, Inherited; Middle Aged; diabetická noha